Makna Kematian pada Wanita Lanjut Usia yang Melajang - Fahmi Mahmudayati Pratiwi; Irfan Fahmi; Anwar Supenawinata (Psympathic : Jurnal Ilmiah Psikologi, 2018)
The purpose of this study is to explore how the meaning of death for subjects who are single elderly women. For humans, death has a double meaning that can be interpreted as a positive thing if humans do good things during their lifetime and can also be interpreted as a negative thing if humans commit bad deeds during their lifetime. This study used a qualitative approach with phenomenology methods. The participant of this study was a single elderly woman. The results in this study indicate that the subject means death as a positive thing, namely by getting closer to the Creator.